Effect of Open and Closed Endotracheal Suction System on Oxygen Saturation Among Mechanically Ventilated Patient: A Comparative Study - Hassan Jaleel, Israa; Abbas Dawood, Hussam (Kerbala Journal of Nursing and Health Sciences., 2025)
Background: Endotracheal suctioning is one of the fundamental procedures practiced in intensive care units. There are two methods used for suctioning: open and closed suction systems. Objective: To compare the effects of open and closed suction system on oxygen saturation among mechanically ventilated patients. Comparative quasi experimental research design was carried out to achieve the study’s objectives . A purposive sample included 80 patients taken from intensive care unit (ICU). Patient appraisal document was utilized for gathering data, which included three parts: bio-demographic data , health relevant data and an assessment sheet to monitor saturation level of oxygen. Results: the results indicates that the closed suctioning has a significant effect on oxygen saturation. After the procedure, oxygen saturation (SpO₂) reduced significantly but recovered completely after 15 minutes, showing a highly significant (p<.001) .Whereas the majority of oxygen saturation is not greatly impacted by the open suction system, which exceeds the statistical significant level (> 0.05). Conclusion: Using a closed suction system reduces fluctuations in oxygen saturation when compared to an open system among patients under mechanical ventilation. Recommendation: Future studies should employ larger sample sizes to enable comparative analysis of suction techniques and their association with acquired infections in intensive care units (ICUs).